2022
DOI: 10.3390/ijms231911394
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Mitochondrial Complex I Dysfunction Correlate with Neurodegeneration in an α-Synucleinopathy Animal Model

Abstract: The α-synucleinopathies constitute a subset of neurodegenerative disorders, of which Parkinson’s disease (PD) is the most common worldwide, characterized by the accumulation of misfolded α-synuclein in the cytoplasm of neurons, which spreads in a prion-like manner to anatomically interconnected brain areas. However, it is not clear how α-synucleinopathy triggers neurodegeneration. We recently developed a rat model through a single intranigral administration of the neurotoxic β-sitosterol β-D-glucoside (BSSG), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…Increasing evidence also supports the pathological role of NLRP3 inflammasome in neurodegeneration based on a mutual association with mitochondrial dysfunction [36,[49][50][51], which correlates with neurodegeneration in parkinsonian rats with α-synucleinopathy [52]. Accordingly, we have shown here that mitochondrial CI dysfunction and NLRP3 activation coincided in the early phase of LPS-induced neuroinflammation and with an increase in nitrosative/oxidative stress, as we previously demonstrated [29].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Increasing evidence also supports the pathological role of NLRP3 inflammasome in neurodegeneration based on a mutual association with mitochondrial dysfunction [36,[49][50][51], which correlates with neurodegeneration in parkinsonian rats with α-synucleinopathy [52]. Accordingly, we have shown here that mitochondrial CI dysfunction and NLRP3 activation coincided in the early phase of LPS-induced neuroinflammation and with an increase in nitrosative/oxidative stress, as we previously demonstrated [29].…”
Section: Discussionsupporting
confidence: 88%
“…The mitochondrial CI activity was determined as reported elsewhere [52]. The tissue from an entire SN was homogenized in PBS pH 7.4 and subsequently centrifugated for 5 min at 2000 g. The supernatants were collected and used to perform the analyses.…”
Section: Mitochondrial Complex I (Ci) Activity Determination In the S...mentioning
confidence: 99%
“…They found that these two parameters of oxidative stress, as well as mitochondrial complex I dysfunction, positively correlate with neurodegeneration in different brain areas with α-synucleinopathy, such as the substantia nigra pars compacta, the striatum, the hippocampus and the olfactory bulb. Based on in silico studies, they suggested the involvement of peroxisome proliferator-activated receptors (PPAR) alpha (PPAR-α) and gamma (PPAR-γ) in this process [98], since PPARs activation induces fatty acid oxidation (which, in turn, generates ROS) [99]. However, this mechanism needs to be further explored.…”
Section: Oxidative Stress In Ageing and Age-related Neurodegenerative...mentioning
confidence: 99%
“…This will promote Cyt C release and caspase-9 activation, which leads to neuronal cell death and facilitating PD pathogenesis ( Figure 2 ; Lin and Beal, 2006 ). Defect in Complex I of the mitochondrial electron transport chain by aggregation of α-synuclein and PTEN-induced putative kinase 1 (PINK1) mutations can be also involved in PD pathogenesis by inducing neuronal apoptosis and failure in maintaining mitochondrial membrane potential, respectively (Liu et al, 2017 ; Morales-Martínez et al, 2022 ).…”
Section: Oxidative Stress-induced Apoptotic Cell Death In Neurodegene...mentioning
confidence: 99%